Synergy between Teachers and Parents of Students in Forming Morals in MI Miftahul Ulum Puntir Students - Nur Ayyuni, Lailah; Kirom, Askhabul; Hadi, Muhammad Nur (Yayasan Rahmat Islamiyah, 2025)
The synergy between Madrasah Ibtidaiyah (MI) and various stakeholders is a key factor in improving the quality of education. This article discusses the collaboration between MI, the government, the community, and other educational institutions in enhancing both learning quality and students' character development. Using a qualitative approach, this study analyzes different forms of synergy as well as the challenges faced in its implementation. The results indicate that effective cooperation between MI and other stakeholders can create a conducive learning environment that supports the development of Islamic values and students' academic competencies. However, there are still challenges in terms of coordination and resources that require further attention. Therefore, a more systematic and sustainable strategy is needed to optimize this synergy.